Strategies for Cultivating Religious Moderation Values at SD NU Kota Metro to Foster Inclusive Student Character - Muhammad Yusuf; Ismail Fahmi (Bulletin of Pedagogical Research, 2025)
This article examines strategies for cultivating the values of religious moderation at SDNU Kota Metro as an effort to foster inclusive student character. The main problem addressed in this study is the absence of a comprehensive operational model at the elementary school level, despite the widely acknowledged theoretical urgency of religious moderation. This research aims to explore how curricular, cultural–behavioral, and institutional policy strategies are implemented, as well as their effectiveness in shaping inclusive character. Drawing on theories of character education, religious moderation, and critical pedagogy, the study employs participatory observation, in-depth interviews, and document analysis. The findings reveal the development of an Integrated Three-Dimensional Strategy Model: (1) a curricular dimension through the teaching of Ahlussunnah wal Jama’ah (ASWAJA) as the theological foundation of moderation; (2) a cultural–behavioral dimension through the practices of 5S (Senyum, Sapa, Salam, Sopan, Santun) and Jum’at Beramal as internalization of empathetic values; and (3) an adaptive-institutional dimension through digital literacy initiatives and art festivals that create inclusive collaborative spaces. The study concludes that religious moderation can be effectively cultivated when it becomes an institutional culture rather than merely instructional content. It recommends strengthening behavior-based evaluation systems, conducting routine critical reflection, and enhancing school–family–community collaboration to ensure the sustainability of inclusive character development